Multi-stage phase-change temperature-adjusting asphalt pavement structure for relieving urban heat island effect

By introducing composite organic eutectic phase change materials with phase change in different wide temperature domains into the upper and lower layers of the asphalt pavement, the multi-stage phase change temperature regulation effect is achieved, and the problem of limited cooling effect of phase change materials in the prior art is solved, which significantly alleviates the urban heat island effect and improves the durability of the pavement.

CN119571691AActive Publication Date: 2025-03-07CHANGAN UNIV

Patent Information

Application Number
CN202411762964.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The cooling effect of existing phase change materials in asphalt pavement is limited, making it difficult to effectively alleviate the urban heat island effect.

Method used

The multi-stage phase change temperature-regulating asphalt pavement structure is adopted. By introducing composite organic eutectic phase change materials with different wide temperature domain phase change into the upper and lower layers, the combination of organic eutectic phase change materials greatly absorbs the heat inside the structure, and targets and customizes the thermal conductivity coefficients of different structural layers to achieve efficient temperature adjustment in the wide temperature domain inside the entire structure.

Benefits of technology

Significantly reduce the temperature of asphalt pavement, extend the time of high temperature of the pavement, alleviate the urban heat island effect, and improve the durability of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571691A_ABST
    Figure CN119571691A_ABST
Patent Text Reader

Abstract

The invention discloses a multistage phase-change temperature-regulating asphalt pavement structure for relieving urban heat island effect, which sequentially comprises an upper surface layer, a lower surface layer, a base layer and a subbase layer from top to bottom, the upper surface layer is formed by a first asphalt mixture doped with a wide-temperature-range phase-change temperature-regulating system A, and the lower surface layer is formed by a second asphalt mixture doped with a wide-temperature-range phase-change temperature-regulating system B; the volume of the wide-temperature-range phase-change temperature-adjusting system A is 7-10% of the volume of the first asphalt mixture, and the wide-temperature-range phase-change temperature-adjusting system A is formed by compounding a plurality of different composite organic eutectic phase-change materials; the lower surface layer is formed by a second asphalt mixture doped with a wide-temperature-range phase-change temperature-adjusting system B, the volume of the wide-temperature-range phase-change temperature-adjusting system B is 5-10% of that of the second asphalt mixture, and the wide-temperature-range phase-change temperature-adjusting system B is formed by compounding a plurality of different composite organic eutectic phase-change materials. The composite organic eutectic phase change materials with different wide temperature range phase changes are introduced into the upper surface layer and the lower surface layer of the asphalt pavement respectively, and heat in the pavement structure can be greatly absorbed through combination of the organic eutectic phase change materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of road engineering, and in particular relates to a multi-stage phase-change temperature-regulating asphalt pavement structure for alleviating urban heat island effect. Background Art

[0002] The urbanization process has caused a serious urban heat island effect (UHI), that is, urban areas are usually hotter than the surrounding rural environment in summer. The main causes of the UHI effect involve the following: the use of special building materials, the complex geometry of urban landscapes, reduced vegetation cover and increased anthropogenic heat emissions. Among these factors, the black asphalt pavement in urban roads has the characteristics of low reflectivity and high heat absorption coefficient, which absorbs a considerable proportion of solar radiation, making the road surface temperature as high as 65°C, which greatly aggravates the UHI effect. The UHI poses considerable health risks to urban residents, mainly involving the risk of heat-related diseases and mortality. In addition, the viscoelasticity and temperature sensitivity of asphalt pavement make it prone to high temperature diseases such as rutting and thermal oxidation aging when exposed to long-term high temperatures, which ultimately affects the durability and serviceability of the road pavement.

[0003] In order to create a livable urban environment, reasonable strategies must be adopted to mitigate urban heat islands. Currently, asphalt pavement designs that integrate renewable energy technologies, such as latent heat structures and photovoltaic materials, have become a promising approach to mitigate urban heat islands. These systems achieve surface temperature reduction by converting absorbed radiation into different types of energy. Phase change materials (PCMs) are functional materials that have the ability to absorb and release thermal energy during phase change, providing a potential solution for regulating temperature changes within pavement structures. When integrated into pavement structure systems, PCMs absorb excess heat energy at the highest temperature reached during the day, thereby significantly reducing the pavement surface temperature, providing a viable strategy to offset urban heat islands. It is feasible to rely on the latent heat properties of phase change materials to give asphalt pavements latent heat capacity, thereby mitigating temperature stress and heat island effects. Obviously, a large number of studies have proved that using the latent heat properties of phase change materials for active pavement temperature control is a feasible approach.

[0004] However, due to the existence of factors such as the single phase change temperature of commonly used phase change materials, the mismatch with the ambient temperature, the low phase change enthalpy value and the unreasonable fusion design, the cooling effect of phase change materials in asphalt pavements is very limited, which greatly restricts their wide application. Therefore, it is urgent to develop a pavement phase change temperature control technology with excellent temperature control performance and significant cooling effect based on the structure of urban asphalt pavements, so as to effectively alleviate the urban heat island effect. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a multi-stage phase change temperature regulating asphalt pavement structure for alleviating the urban heat island effect. The technical problem to be solved by the present invention is achieved through the following technical solutions:

[0006] The present invention provides a multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect, which comprises an upper layer, a lower layer, a base layer and a subbase layer from top to bottom, wherein:

[0007] The upper layer is formed by a first asphalt mixture mixed with a wide temperature range phase change temperature regulating system A, the volume of the wide temperature range phase change temperature regulating system A is 7-10% of the volume of the first asphalt mixture, and the wide temperature range phase change temperature regulating system A is compounded by 5 different composite organic eutectic phase change materials;

[0008] The lower layer is formed by a second asphalt mixture mixed with a wide temperature range phase change temperature regulation system B, the volume of the wide temperature range phase change temperature regulation system B is 5 to 10% of the volume of the second asphalt mixture, and the wide temperature range phase change temperature regulation system B is compounded from 4 different composite organic eutectic phase change materials.

[0009] In one embodiment of the present invention, the wide temperature range phase change temperature adjustment system A comprises 45 to 55 parts by mass of a composite organic eutectic phase change material A-1, 360 to 440 parts by mass of a composite organic eutectic phase change material, 270 to 330 parts by mass of a composite organic eutectic phase change material A-3, 180 to 220 parts by mass of a composite organic eutectic phase change material A-4, and 45 to 55 parts by mass of a composite organic eutectic phase change material A-5, wherein:

[0010] The raw materials of the composite organic eutectic phase change material A-1 are 180 to 220 parts by mass of stearic acid, 270 to 330 parts by mass of palmitic acid, 440 to 540 parts by mass of myristic acid and 90 to 110 parts by mass of expanded graphite;

[0011] The raw materials of the composite organic eutectic phase change material A-2 are 260 to 320 parts by mass of stearic acid, 650 to 790 parts by mass of myristic acid and 90 to 110 parts by mass of expanded graphite;

[0012] The raw materials of the composite organic eutectic phase change material A-3 are 360 ​​to 440 parts by mass of stearic acid, 540 to 660 parts by mass of palmitic acid and 90 to 110 parts by mass of expanded graphite;

[0013] The raw materials of the composite organic eutectic phase change material A-4 are 25 to 35 parts by mass of adipic acid, 50 to 60 parts by mass of sebacic acid, 800 to 1000 parts by mass of palmitic acid and 90 to 110 parts by mass of expanded graphite;

[0014] The raw materials of the composite organic eutectic phase change material A-5 are 20 to 40 parts by mass of adipic acid, 60 to 75 parts by mass of sebacic acid, 800 to 1000 parts by mass of stearic acid and 90 to 110 parts by mass of expanded graphite.

[0015] In one embodiment of the present invention, the preparation process of the composite organic eutectic phase change material A-1 includes:

[0016] 180-220 parts by mass of stearic acid, 270-330 parts by mass of palmitic acid and 440-540 parts by mass of myristic acid are mixed and heated until completely melted, and stirred until completely mixed to form a blended mixture;

[0017] Adding 90 to 110 parts by weight of expanded expanded graphite to the blended mixture, stirring and adsorbing for 4 to 6 hours in a vacuum environment of 70 to 90° C., and then placing the mixture in a vacuum drying oven to continue adsorbing for 40 to 55 hours;

[0018] The adsorbed mixture was taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain the composite organic eutectic phase change material A-1.

[0019] In one embodiment of the present invention, the wide temperature range phase change temperature adjustment system B comprises: 90 to 110 parts by mass of composite organic eutectic phase change material B-1, 90 to 110 parts by mass of composite organic eutectic phase change material B-2, 450 to 550 parts by mass of composite organic eutectic phase change material B-3 and 270 to 330 parts by mass of composite organic eutectic phase change material B-4, wherein:

[0020] The raw materials of the composite organic eutectic phase change material B-1 are 135-165 parts by mass of palmitic acid, 220-270 parts by mass of myristic acid, 540-660 parts by mass of methyl stearate, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite;

[0021] The raw materials of the composite organic eutectic phase change material B-2 are 130-170 parts by mass of palmitic acid, 770-930 parts by mass of methyl stearate, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite;

[0022] The raw materials of the composite organic eutectic phase change material B-3 are 180-220 parts by mass of stearic acid, 270-330 parts by mass of palmitic acid, 450-550 parts by mass of myristic acid, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite;

[0023] The raw materials of the composite organic eutectic phase change material B-4 are 260-320 parts by mass of stearic acid, 640-780 parts by mass of myristic acid, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite.

[0024] In one embodiment of the present invention, the preparation process of the composite organic eutectic phase change material B-1 includes:

[0025] 135-165 parts by mass of palmitic acid, 220-270 parts by mass of myristic acid, and 540-660 parts by mass of methyl stearate are mixed and heated until completely melted, and then 35-55 parts by mass of multi-walled carbon nanotubes and 55-65 parts by mass of layered graphene oxide are added, and stirred until completely mixed to form a blended mixture;

[0026] Add 70 to 90 parts by weight of expanded graphite and 90 to 110 parts by weight of silane coupling agent to the blended mixture, stir and adsorb for 4 to 6 hours in a vacuum environment at 70 to 90° C., and then place in a vacuum drying oven to continue adsorbing for 40 to 55 hours;

[0027] The adsorbed mixture was taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain the composite organic eutectic phase change material B-1.

[0028] In one embodiment of the present invention, the thickness of the upper layer is 4 to 6 cm, and the thickness of the lower layer is 6 to 8 cm.

[0029] In one embodiment of the present invention, the asphalt in the first asphalt mixture and the second asphalt mixture are both SBS modified asphalt.

[0030] In one embodiment of the present invention, the first asphalt mixture is AC-13 asphalt mixture; the second asphalt mixture is AC-20 asphalt mixture.

[0031] In one embodiment of the present invention, the base layer is composed of two layers of cement-stabilized crushed stone with a thickness of 30 to 34 cm.

[0032] In one embodiment of the present invention, the base layer is composed of lime soil and has a thickness of 18 to 22 cm.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention focuses on the urban heat island effect and rutting problems caused by high temperatures in urban asphalt pavements in summer, and provides a multi-stage phase change temperature regulating asphalt pavement structure that alleviates the urban heat island effect. The pavement structure introduces composite organic eutectic phase change materials with different wide temperature range phase changes in the upper and lower layers of the asphalt pavement, respectively, and utilizes the combination of organic eutectic phase change materials to absorb the heat inside the structure to a large extent; at the same time, the present invention fully considers the tasks and differentiated heat transfer characteristics of different structural layers during service, and targets and customizes the thermal conductivity of organic eutectic phase change materials for different structural layers; in order to achieve wide temperature range and efficient temperature regulation inside the entire structure, maximize the release of the latent heat capacity of phase change, and achieve the purpose of reducing the temperature of the asphalt pavement and prolonging the high temperature effect of the pavement, thereby alleviating the urban heat island effect and prolonging the durability of the pavement.

[0035] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a module diagram of a multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect provided by an embodiment of the present invention;

[0037] Figure 2 This is a schematic diagram of a specific structure of a multi-stage phase-change temperature-adjustable asphalt pavement structure for alleviating the urban heat island effect provided by an embodiment of the present invention;

[0038] Figure 3 is a cross-sectional view of a multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect provided by an embodiment of the present invention;

[0039] Figure 4 It is a schematic diagram of temperature field curves of different implementation cases provided by the embodiments of the present invention. DETAILED DESCRIPTION

[0040] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a multi-stage phase change temperature regulating asphalt pavement structure for alleviating the urban heat island effect proposed by the present invention in combination with the accompanying drawings and specific implementation methods.

[0041] The above and other technical contents, features and effects of the present invention are clearly presented in the following detailed description of the specific implementation modes in conjunction with the accompanying drawings. Through the description of the specific implementation modes, the technical means and effects adopted by the present invention to achieve the predetermined purpose can be more deeply and specifically understood. However, the attached drawings are only for reference and explanation purposes and are not used to limit the technical solutions of the present invention.

[0042] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants are intended to cover non-exclusive inclusion, so that an article or device including a series of elements includes not only those elements, but also other elements that are not explicitly listed. In the absence of more restrictions, the elements defined by the statement "including one..." do not exclude the existence of other identical elements in the article or device including the elements.

[0043] Embodiment 1

[0044] The embodiment of the present invention provides a multi-stage phase change temperature regulating asphalt pavement structure for alleviating the urban heat island effect, such as Figures 1 to 3 As shown, the multi-level phase change temperature regulating asphalt pavement structure includes an upper layer, a lower layer, a base layer and a subbase layer from top to bottom, wherein the upper layer is formed by a first asphalt mixture mixed with a wide temperature range phase change temperature regulating system A, the volume of the wide temperature range phase change temperature regulating system A is 7-10% of the volume of the first asphalt mixture, and the wide temperature range phase change temperature regulating system A is compounded by 5 different composite organic eutectic phase change materials; the lower layer is formed by a second asphalt mixture mixed with a wide temperature range phase change temperature regulating system B, the volume of the wide temperature range phase change temperature regulating system B is 5-10% of the volume of the second asphalt mixture, and the wide temperature range phase change temperature regulating system B is compounded by 4 different composite organic eutectic phase change materials.

[0045] The thickness of the upper layer of this embodiment can be 4-6 cm, the thickness of the lower layer can be 6-8 cm, the base layer is composed of two 15-17 cm cement-stabilized gravel layers, and the total thickness of the base layer can be 30-34 cm; the subbase layer is composed of 18-22 cm lime soil.

[0046] The first asphalt mixture of this embodiment is AC-13 asphalt mixture, and the second asphalt mixture is AC-20 asphalt mixture. In other embodiments, the first asphalt mixture and the second asphalt mixture can also be selected from other suitable asphalt mixtures according to actual conditions.

[0047] Furthermore, the wide temperature range phase change temperature control system A of the present embodiment is compounded by 5 different composite organic eutectic phase change materials, specifically including 45 to 55 parts by mass of composite organic eutectic phase change material A-1, 360 to 440 parts by mass of composite organic eutectic phase change material, 270 to 330 parts by mass of composite organic eutectic phase change material A-3, 180 to 220 parts by mass of composite organic eutectic phase change material A-4 and 45 to 55 parts by mass of composite organic eutectic phase change material A-5.

[0048] Specifically, the raw materials of the composite organic eutectic phase change material A-1 are 180 to 220 parts by mass of stearic acid, 270 to 330 parts by mass of palmitic acid, 440 to 540 parts by mass of myristic acid, and 90 to 110 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-2 are 260 to 320 parts by mass of stearic acid, 650 to 790 parts by mass of myristic acid, and 90 to 110 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-3 are 360 ​​to 440 parts by mass of stearic acid, The raw materials of the composite organic eutectic phase change material A-4 are 25-35 parts by mass of adipic acid, 50-60 parts by mass of sebacic acid, 800-1000 parts by mass of palmitic acid and 90-110 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-5 are 20-40 parts by mass of adipic acid, 60-75 parts by mass of sebacic acid, 800-1000 parts by mass of stearic acid and 90-110 parts by mass of expanded graphite.

[0049] The preparation process of the composite organic eutectic phase change material A-1 of this embodiment includes:

[0050] 180-220 parts by mass of stearic acid, 270-330 parts by mass of palmitic acid and 440-540 parts by mass of myristic acid are mixed and heated until completely melted, and stirred until completely mixed to form a blended mixture; 90-110 parts by mass of expanded expanded graphite are added to the blended mixture, and the mixture is stirred and adsorbed for 4-6 hours in a vacuum environment of 70-90° C., and then placed in a vacuum drying oven to continue adsorption for 40-55 hours; the adsorbed mixture is taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain a composite organic eutectic phase change material A-1.

[0051] Similar to the preparation process of the composite organic eutectic phase change material A-1, the composite organic eutectic phase change materials A-2 to A-5 are prepared by simply replacing different organic phase change materials in corresponding proportions. Exemplarily, the preparation process of the composite organic eutectic phase change material A-2 includes:

[0052] 260-320 parts by mass of stearic acid and 650-790 parts by mass of myristic acid are mixed and heated until completely melted, and stirred until completely mixed to form a blended mixture; 90-110 parts by mass of expanded expanded graphite are added to the blended mixture, and the mixture is stirred and adsorbed for 4-6 hours in a vacuum environment of 70-90° C., and then placed in a vacuum drying oven to continue adsorption for 40-55 hours; the adsorbed mixture is taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain a composite organic eutectic phase change material A-2.

[0053] The preparation process of the composite organic eutectic phase change materials A-3 to A-5 is the same as the above preparation process, which will not be repeated here.

[0054] Furthermore, the preparation method of the upper layer of this embodiment comprises the following steps:

[0055] Design an AC-13 type asphalt mixture; directly add the above-prepared wide temperature range phase change temperature regulating system A to the AC-13 type asphalt mixture at a volume fraction of 7 to 10% of the asphalt mixture by external mixing method, and mix by conventional mixing method to obtain the material for paving the upper layer. It should be noted that the asphalt in the AC-13 type asphalt mixture needs to be SBS modified asphalt.

[0056] The wide temperature range phase change temperature control system B of the present embodiment comprises: 90-110 parts by mass of composite organic eutectic phase change material B-1, 90-110 parts by mass of composite organic eutectic phase change material B-2, 450-550 parts by mass of composite organic eutectic phase change material B-3 and 270-330 parts by mass of composite organic eutectic phase change material B-4, wherein the raw materials of composite organic eutectic phase change material B-1 are 135-165 parts by mass of palmitic acid, 220-270 parts by mass of myristic acid, 540-660 parts by mass of methyl stearate, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded expanded graphite; the raw materials of composite organic eutectic phase change material B-2 are 130-170 parts by mass of palmitic acid, 770-930 parts by mass of 0 parts by mass of methyl stearate, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material B-3 are 180-220 parts by mass of stearic acid, 270-330 parts by mass of palmitic acid, 450-550 parts by mass of myristic acid, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material B-4 are 260-320 parts by mass of stearic acid, 640-780 parts by mass of myristic acid, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite.

[0057] Specifically, the preparation process of the composite organic eutectic phase change material B-1 of this embodiment includes:

[0058] 135-165 parts by mass of palmitic acid, 220-270 parts by mass of myristic acid, and 540-660 parts by mass of methyl stearate are mixed and heated until completely melted, and then 35-55 parts by mass of multi-walled carbon nanotubes and 55-65 parts by mass of layered graphene oxide are added, and stirred until completely mixed to form a blended mixture; 70-90 parts by mass of expanded graphite and 90-110 parts by mass of silane coupling agent are added to the blended mixture, and stirred and adsorbed for 4-6 hours in a vacuum environment of 70-90° C., and then placed in a vacuum drying oven for continued adsorption for 40-55 hours; the adsorbed mixture is taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain a composite organic eutectic phase change material B-1.

[0059] Similar to the preparation process of the composite organic eutectic phase change material B-1, the composite organic eutectic phase change materials B-2 to B-4 are prepared by simply replacing different organic phase change materials in corresponding proportions. Exemplarily, the preparation process of the composite organic eutectic phase change material B-2 includes:

[0060] 130-170 parts by mass of palmitic acid and 770-930 parts by mass of methyl stearate are mixed and heated until completely melted, and then 35-55 parts by mass of multi-walled carbon nanotubes and 55-65 parts by mass of layered graphene oxide are added, and stirred until completely mixed to form a blended mixture; 70-90 parts by mass of expanded graphite and 90-110 parts by mass of silane coupling agent are added to the blended mixture, and stirred and adsorbed for 4-6 hours in a vacuum environment of 70-90° C., and then placed in a vacuum drying oven to continue adsorption for 40-55 hours; the adsorbed mixture is taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain a composite organic eutectic phase change material B-2.

[0061] The preparation process of the composite organic eutectic phase change material B-3 to the composite organic eutectic phase change material B-4 is the same as the above preparation process, which will not be repeated here.

[0062] Further, the preparation method of the following layer comprises the following steps:

[0063] Design AC-20 asphalt mixture; directly add wide temperature range phase change temperature regulating system B into AC-20 asphalt mixture by external mixing method at 5-10% of asphalt mixture volume fraction; mix by conventional mixing method to obtain material for paving the upper layer. It should be noted that the asphalt in the AC-20 asphalt mixture needs to be SBS modified asphalt.

[0064] Embodiment 2

[0065] On the basis of Example 1, this embodiment provides a specific example of a multi-level phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect. The multi-level phase-change temperature-adjusting asphalt pavement structure includes an upper layer, a lower layer, a base layer and a subbase layer from top to bottom, wherein the upper layer is formed by a first asphalt mixture mixed with a wide temperature range phase-change temperature-adjusting system A, the volume of the wide temperature range phase-change temperature-adjusting system A is 10% of the volume of the first asphalt mixture, and the wide temperature range phase-change temperature-adjusting system A is compounded from 5 different composite organic eutectic phase change materials; the lower layer is formed by a second asphalt mixture mixed with a wide temperature range phase-change temperature-adjusting system B, the volume of the wide temperature range phase-change temperature-adjusting system B is 10% of the volume of the second asphalt mixture, and the wide temperature range phase-change temperature-adjusting system B is compounded from 4 different composite organic eutectic phase change materials.

[0066] The thickness of the upper layer of this embodiment is 5 cm, the thickness of the lower layer is 7 cm, the base layer is composed of two 16 cm cement-stabilized crushed stone layers, and the subbase layer is composed of 20 cm lime soil. The first asphalt mixture of this embodiment is AC-13 asphalt mixture, and the second asphalt mixture is AC-20 asphalt mixture.

[0067] Furthermore, the wide temperature range phase change temperature control system A of the present embodiment is compounded by 5 different composite organic eutectic phase change materials, specifically including 50 parts by mass of composite organic eutectic phase change material A-1, 400 parts by mass of composite organic eutectic phase change material, 300 parts by mass of composite organic eutectic phase change material A-3, 200 parts by mass of composite organic eutectic phase change material A-4 and 50 parts by mass of composite organic eutectic phase change material A-5.

[0068] Specifically, the raw materials of the composite organic eutectic phase change material A-1 of this embodiment are 203 parts by mass of stearic acid, 307 parts by mass of palmitic acid, 490 parts by mass of myristic acid and 100 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-2 are 286 parts by mass of stearic acid, 724 parts by mass of myristic acid and 100 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-3 are 397 parts by mass of stearic acid, 603 parts by mass of palmitic acid and 100 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-4 are 27 parts by mass of adipic acid, 55 parts by mass of sebacic acid and 918 parts by mass of palmitic acid and 100 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material A-5 are 33 parts by mass of adipic acid, 66 parts by mass of sebacic acid, 900 parts by mass of stearic acid and 100 parts by mass of expanded graphite.

[0069] The preparation process of the composite organic eutectic phase change material A-1 of this embodiment includes:

[0070] 203 parts of stearic acid, 307 parts of palmitic acid and 490 parts of myristic acid were mixed and heated until completely melted, and stirred at a speed of 300 rad / min for 4 hours, and then 100 parts of expanded graphite with a particle size of 50 mesh were added to the blended mixture; then the above mixture was stirred and adsorbed at 80°C in a vacuum environment for 5 hours, and then placed in a vacuum drying oven to continue adsorption for 48 hours; then the adsorbed mixture was taken out, and stirred and rinsed with anhydrous ethanol for 5 times; finally, it was placed in an oven at 80°C and dried for 24 hours to obtain a composite organic eutectic phase change material A-1.

[0071] Similar to the preparation process of the composite organic eutectic phase change material A-1, composite organic eutectic phase change materials A-2 to A-5 are prepared by simply replacing different organic phase change materials in corresponding proportions.

[0072] Exemplarily, the preparation process of the composite organic eutectic phase change material A-2 includes:

[0073] 286 parts of stearic acid and 724 parts of myristic acid were mixed and heated until completely melted, and stirred at a speed of 300 rad / min for 4 hours, and then 100 parts of expanded graphite with a particle size of 50 mesh were added to the blended mixture; then the above mixture was stirred and adsorbed at 80°C in a vacuum environment for 5 hours, and then placed in a vacuum drying oven to continue adsorption for 48 hours; then the adsorbed mixture was taken out, and stirred and rinsed with anhydrous ethanol for 5 times; finally, it was placed in an oven at 80°C and dried for 24 hours to obtain a composite organic eutectic phase change material A-2.

[0074] The preparation process of the composite organic eutectic phase change materials A-3 to A-5 is the same as the above preparation process, which will not be repeated here.

[0075] Furthermore, the preparation method of the upper layer comprises the following steps:

[0076] Design an AC-13 type asphalt mixture; according to the external mixing method, directly add the above-prepared wide temperature range phase change temperature regulating system A to the AC-13 type asphalt mixture at a volume fraction of 10% of the asphalt mixture, and mix it according to the conventional mixing method to obtain the material for paving the upper layer. It should be noted that the asphalt in the AC-13 type asphalt mixture must be SBS modified asphalt.

[0077] The wide temperature range phase change temperature control system B of this embodiment includes: 100 parts by mass of composite organic eutectic phase change material B-1, 100 parts by mass of composite organic eutectic phase change material B-2, 500 parts by mass of composite organic eutectic phase change material B-3 and 300 parts by mass of composite organic eutectic phase change material B-4, wherein the raw materials of composite organic eutectic phase change material B-1 are 153 parts by mass of palmitic acid, 243 parts by mass of myristic acid, 604 parts by mass of methyl stearate, 40 parts by mass of multi-walled carbon nanotubes, 60 parts by mass of layered graphene oxide and 80 parts by mass of expanded expanded graphite; the raw materials of composite organic eutectic phase change material B-2 are 148 parts by mass of palmitic acid, 852 parts by mass of methyl stearate, 40 parts by mass of multi-walled carbon nanotubes, 60 parts by mass of layered graphene oxide and 80 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material B-3 are 203 parts by mass of stearic acid, 307 parts by mass of palmitic acid, 490 parts by mass of myristic acid, 40 parts by mass of multi-walled carbon nanotubes, 60 parts by mass of layered graphene oxide and 80 parts by mass of expanded graphite; the raw materials of the composite organic eutectic phase change material B-4 are 286 parts by mass of stearic acid, 724 parts by mass of myristic acid, 40 parts by mass of multi-walled carbon nanotubes, 60 parts by mass of layered graphene oxide and 80 parts by mass of expanded graphite.

[0078] Furthermore, the preparation process of the composite organic eutectic phase change material B-1 includes:

[0079] 153 parts of palmitic acid, 243 parts of myristic acid and 604 parts of methyl stearate were mixed and heated until completely melted, and then 40 parts of multi-walled carbon nanotubes and 60 parts of layered graphene oxide were added, and the mixture was stirred and mixed at 300 rad / min for 4 hours. Then, 80 parts of expanded expanded graphite and 100 parts of silane coupling agent were added to the blended mixture; the above mixture was stirred and adsorbed at 80°C vacuum environment for 5 hours, and then placed in a vacuum drying oven to continue adsorption for 48 hours; the adsorbed mixture was taken out, and it was stirred and rinsed with anhydrous ethanol for 5 times; finally, it was placed in an oven at 80°C and dried for 24 hours to obtain a composite organic eutectic phase change material B-1.

[0080] According to the above method, composite organic eutectic phase change materials B-2 to B-4 are prepared by simply replacing different organic phase change materials in corresponding proportions.

[0081] Exemplarily, the preparation process of the composite organic eutectic phase change material B-2 is specifically as follows:

[0082] 148 parts of palmitic acid and 852 parts of methyl stearate were mixed and heated until completely melted, and then 40 parts of multi-walled carbon nanotubes and 60 parts of layered graphene oxide were added, and the mixture was stirred and mixed at a speed of 300 rad / min for 4 hours, and then 80 parts of expanded expanded graphite were added to the blended mixture, and 100 parts of silane coupling agent were added; the above mixture was stirred and adsorbed at 80°C vacuum environment for 5 hours, and then placed in a vacuum drying oven to continue adsorption for 48 hours; the adsorbed mixture was taken out, and it was stirred and rinsed with anhydrous ethanol for 5 times; finally, it was placed in an oven at 80°C and dried for 24 hours to obtain a composite organic eutectic phase change material B-2.

[0083] The preparation process of the composite organic eutectic phase change material B-3 to the composite organic eutectic phase change material B-4 is the same as the above preparation process, which will not be repeated here.

[0084] Further, the preparation method of the following layer comprises the following steps:

[0085] Design an AC-20 type asphalt mixture; directly add the wide temperature range phase change temperature regulating system B to the AC-20 type asphalt mixture according to the external mixing method at a volume fraction of 7% of the asphalt mixture; mix according to the conventional mixing method to obtain the material for paving the upper layer. It should be noted that the asphalt in the AC-20 type asphalt mixture must be SBS modified asphalt.

[0086] The present invention focuses on the urban heat island effect and rutting problems caused by high temperatures in urban asphalt pavements in summer, and provides a multi-stage phase change temperature-adjusting asphalt pavement structure that alleviates the urban heat island effect. The structure introduces composite organic eutectic phase change materials with different wide temperature range phase changes in the upper and lower layers of the asphalt pavement, respectively, and utilizes the combination of organic eutectic phase change materials to absorb the heat inside the structure to a large extent; at the same time, the present invention fully considers the tasks and differentiated heat transfer characteristics of different structural layers during service, and targets and customizes the thermal conductivity of organic eutectic phase change materials for different structural layers; in order to achieve wide temperature range and efficient temperature adjustment inside the entire structure, maximize the release of the latent heat capacity of phase change, and achieve the purpose of reducing the temperature of the asphalt pavement and prolonging the high temperature effect of the pavement, thereby alleviating the urban heat island effect and prolonging the durability of the pavement.

[0087] The multi-stage phase change temperature regulating asphalt pavement structure provided by the present invention is further described below with reference to specific examples, but the present invention is not limited to the following examples.

[0088] Implementation Case 1

[0089] In this example, the upper layer uses AC-13 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After the addition of mineral powder, the wide temperature range phase change temperature control system A prepared in the above embodiment 2 is added according to 7% of the volume of the asphalt mixture; the lower layer uses AC-20 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After the addition of mineral powder, the wide temperature range phase change temperature control system B prepared in the above embodiment 2 is added according to 5% of the volume of the asphalt mixture.

[0090] Implementation Case 2

[0091] In this example, the upper layer uses AC-13 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After the addition of mineral powder, the wide temperature range phase change temperature control system A prepared in the above embodiment 2 is added according to 8% of the volume of the asphalt mixture; the lower layer uses AC-20 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After the addition of mineral powder, the wide temperature range phase change temperature control system B prepared in the above embodiment 2 is added according to 6% of the volume of the asphalt mixture.

[0092] Implementation Case 3

[0093] In this example, the upper layer uses AC-13 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After the addition of mineral powder, the wide temperature range phase change temperature control system A prepared in the above embodiment 2 is added according to 9% of the volume of the asphalt mixture; the lower layer uses AC-20 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After the addition of mineral powder, the wide temperature range phase change temperature control system B prepared in the above embodiment 2 is added according to 7% of the volume of the asphalt mixture.

[0094] Implementation Case 4

[0095] In the design, the upper layer uses AC-13 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After adding mineral powder, the wide temperature range phase change temperature control system A prepared in the above embodiment 2 is added according to 10% of the volume of the asphalt mixture; the lower layer uses AC-20 asphalt mixture, and the asphalt mixture is prepared and related test specimens are formed according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E-20-2011). After adding mineral powder, the wide temperature range phase change temperature control system B prepared in the above embodiment 2 is added according to 8% of the volume of the asphalt mixture.

[0096] Taking the samples without phase change materials as the control group, the performance of different implementation cases is shown in Table 1. It can be seen from Table 1 that the rutting depths in the four different implementation cases are 3.64mm, 3.23mm, 2.54mm and 1.96mm respectively. These rutting depths are significantly lower than the 14.98mm of the AC-13 asphalt mixture (control group), with the maximum reduction of about 7.6 times. The final rutting depth of the asphalt mixture is usually related to its rutting resistance. The lower the rutting depth, the better its resistance to permanent deformation. Obviously, the introduction of a wide temperature range phase change temperature control system into the asphalt mixture makes it show more outstanding resistance to rutting and water damage. Furthermore, the temperature field of the pavement structure under different implementation cases was simulated by ABAQUS finite element simulation software. The temperature field simulation results are shown in the figure. Figure 4 As shown in the figure, the pavement structure represents the control group without adding phase change materials. Figure 4 It can be seen that with the increase of the depth of the pavement structure, the temperature conditions in the four implementation cases show a decreasing trend, which means the downward decreasing characteristics of heat transfer in the pavement structure. It is worth noting that at the same depth, the temperature curve of the multi-stage phase change temperature regulating asphalt pavement structure is always lower than that of the traditional type of asphalt pavement structure between about 8:00 and 16:00. At the same time, as the depth of the pavement structure increases, the temperature difference is gradually reduced, and the temperature change also shows a lag phenomenon. Specifically, by Figure 4 From the temperature difference curve in , it can be seen that the negative temperature difference action time of the multi-stage phase change temperature regulating asphalt pavement structure is about 7 hours, and the maximum temperature difference is about 7°C (the bottom of the upper layer of Implementation Case 4).

[0097] Table 1 Hamburger rutting test results of different samples

[0098] Sample Rutting depth (mm) AC-13 asphalt mixture (control group) 14.98 Implementation Case 1: Asphalt mixture on the upper layer 3.64 Implementation Case 2: Asphalt mixture on the upper layer 3.23 Implementation case 3: Asphalt mixture on the upper layer 2.54 Implementation Case 4: Asphalt mixture on the upper layer 1.96

[0099] The daily maximum temperatures of the road surface, the bottom of the upper layer, and the bottom of the lower layer are shown in Table 2. It can be seen from Table 2 that for the daily maximum temperature of the asphalt pavement, the daily maximum temperatures of the four different multi-stage phase change temperature-adjusting asphalt pavement implementation cases are significantly lower than the corresponding points of the traditional asphalt pavement. On the road surface, the daily maximum temperatures of the four different implementation cases were 61.82℃, 60.78℃, 60.38℃, and 60.21℃, respectively, which were 2.98℃, 4.02℃, 4.42℃, and 4.59℃ lower than the control group, respectively. Similarly, the maximum temperature difference of the daily maximum temperature at the bottom of the upper layer and the bottom of the lower layer was 6.96℃ and 4.94℃, respectively.

[0100] Table 2. Simulation results of daily maximum temperature

[0101]

[0102] The phase change endothermic process of the wide temperature range phase change temperature control system A provided by the present invention can cover 40℃~70℃, involves a multi-stage phase change process, and can fully match the summer temperature condition of the upper layer of the urban asphalt pavement, and at the same time, the thermal conductivity is low, so that the phase change process can be continuously and effectively carried out. At the same time, the phase change endothermic process of the wide temperature range phase change temperature control system B can cover 30℃~50℃, fully match the summer temperature condition of the lower layer of the urban asphalt pavement, and has a high thermal conductivity. While the multi-stage phase change endothermic reaction is in progress, the heat of the lower layer can be quickly transferred to the roadbed.

[0103] The combination of wide temperature range multi-stage phase change of the upper layer and the lower layer can effectively absorb most of the heat inside the pavement structure and quickly transfer the heat inside the surface structure to the roadbed. Through the method of numerical simulation, the pavement structure of the present invention can continuously reduce the overall pavement temperature for a duration of 10 hours, with a maximum temperature difference of 8°C, reduce the daily maximum temperature of each structural layer of the asphalt pavement by up to 7°C, and delay the occurrence of the daily maximum temperature by 2 hours; at the same time, the pavement rutting performance is improved by 300%. Thereby achieving the purpose of alleviating the urban heat island effect and improving the durability of the pavement.

[0104] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect, characterized in that: From top to bottom, it includes the upper layer, the lower layer, the base layer and the subbase layer, among which: The upper layer is formed by a first asphalt mixture mixed with a wide temperature range phase change temperature regulating system A, the volume of the wide temperature range phase change temperature regulating system A is 7-10% of the volume of the first asphalt mixture, and the wide temperature range phase change temperature regulating system A is compounded by a plurality of different composite organic eutectic phase change materials; The lower layer is formed by a second asphalt mixture mixed with a wide temperature range phase change temperature control system B, the volume of the wide temperature range phase change temperature control system B is 5 to 10% of the volume of the second asphalt mixture, and the wide temperature range phase change temperature control system B is compounded from a variety of different composite organic eutectic phase change materials.

2. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 1 is characterized in that: The wide temperature range phase change temperature control system A comprises 45 to 55 parts by mass of a composite organic eutectic phase change material A-1, 360 to 440 parts by mass of a composite organic eutectic phase change material, 270 to 330 parts by mass of a composite organic eutectic phase change material A-3, 180 to 220 parts by mass of a composite organic eutectic phase change material A-4, and 45 to 55 parts by mass of a composite organic eutectic phase change material A-5, wherein: The raw materials of the composite organic eutectic phase change material A-1 are 180 to 220 parts by mass of stearic acid, 270 to 330 parts by mass of palmitic acid, 440 to 540 parts by mass of myristic acid and 90 to 110 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material A-2 are 260 to 320 parts by mass of stearic acid, 650 to 790 parts by mass of myristic acid and 90 to 110 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material A-3 are 360 ​​to 440 parts by mass of stearic acid, 540 to 660 parts by mass of palmitic acid and 90 to 110 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material A-4 are 25 to 35 parts by mass of adipic acid, 50 to 60 parts by mass of sebacic acid, 800 to 1000 parts by mass of palmitic acid and 90 to 110 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material A-5 are 20 to 40 parts by mass of adipic acid, 60 to 75 parts by mass of sebacic acid, 800 to 1000 parts by mass of stearic acid and 90 to 110 parts by mass of expanded graphite.

3. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 2 is characterized in that: The preparation process of the composite organic eutectic phase change material A-1 includes: 180-220 parts by mass of stearic acid, 270-330 parts by mass of palmitic acid and 440-540 parts by mass of myristic acid are mixed and heated until completely melted, and stirred until completely mixed to form a blended mixture; Adding 90 to 110 parts by weight of expanded expanded graphite to the blended mixture, stirring and adsorbing for 4 to 6 hours in a vacuum environment of 70 to 90° C., and then placing the mixture in a vacuum drying oven to continue adsorbing for 40 to 55 hours; The adsorbed mixture was taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain the composite organic eutectic phase change material A-1.

4. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 1 is characterized in that: The wide temperature range phase change temperature control system B comprises 90-110 parts by mass of composite organic eutectic phase change material B-1, 90-110 parts by mass of composite organic eutectic phase change material B-2, 450-550 parts by mass of composite organic eutectic phase change material B-3 and 270-330 parts by mass of composite organic eutectic phase change material B-4, wherein: The raw materials of the composite organic eutectic phase change material B-1 are 135-165 parts by mass of palmitic acid, 220-270 parts by mass of myristic acid, 540-660 parts by mass of methyl stearate, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material B-2 are 130-170 parts by mass of palmitic acid, 770-930 parts by mass of methyl stearate, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material B-3 are 180-220 parts by mass of stearic acid, 270-330 parts by mass of palmitic acid, 450-550 parts by mass of myristic acid, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite; The raw materials of the composite organic eutectic phase change material B-4 are 260-320 parts by mass of stearic acid, 640-780 parts by mass of myristic acid, 35-55 parts by mass of multi-walled carbon nanotubes, 55-65 parts by mass of layered graphene oxide and 70-90 parts by mass of expanded graphite.

5. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 4 is characterized in that: The preparation process of the composite organic eutectic phase change material B-1 includes: 135-165 parts by mass of palmitic acid, 220-270 parts by mass of myristic acid, and 540-660 parts by mass of methyl stearate are mixed and heated until completely melted, and then 35-55 parts by mass of multi-walled carbon nanotubes and 55-65 parts by mass of layered graphene oxide are added, and stirred until completely mixed to form a blended mixture; Add 70 to 90 parts by weight of expanded graphite and 90 to 110 parts by weight of a silane coupling agent to the blended mixture, stir and adsorb for 4 to 6 hours in a vacuum environment at 70 to 90° C., and then place in a vacuum drying oven to continue adsorbing for 40 to 55 hours; The adsorbed mixture was taken out, stirred and rinsed with anhydrous ethanol for multiple times, and placed in an oven for drying to obtain the composite organic eutectic phase change material B-1.

6. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 1 is characterized in that: The thickness of the upper layer is 4 to 6 cm, and the thickness of the lower layer is 6 to 8 cm.

7. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 1 is characterized in that: The asphalt in the first asphalt mixture and the second asphalt mixture are both SBS modified asphalt.

8. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to claim 1 is characterized in that: The first asphalt mixture is AC-13 asphalt mixture; the second asphalt mixture is AC-20 asphalt mixture.

9. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to any one of claims 1 to 8, characterized in that: The base layer is composed of two layers of cement-stabilized crushed stone with a thickness of 30 to 34 cm.

10. The multi-stage phase-change temperature-adjusting asphalt pavement structure for alleviating the urban heat island effect according to any one of claims 1 to 8, characterized in that: The base layer is composed of lime soil and has a thickness of 18 to 22 cm.

Citation Information

Patent Citations

  • Powdery diatomite composite phase-change material and preparation method thereof

    CN102746824A

  • High-performance composite phase-change material and preparation method thereof

    CN108251063A

  • Preparation method of tetradecane expanded graphite low-temperature phase-change cement mortar

    CN111592303A

  • Bituminous pavement structure with double-layer phase-change temperature regulation function

    CN114108415A

  • Double-temperature-range phase-change rigid polyurethane foam composite material and preparation method thereof

    CN114891176A

Cited By

  • Self-temperature-adjusting and tail gas purifying type ecological asphalt pavement structure and construction method thereof

    CN121896871A